Autoinflammatory and autoimmune conditions at the crossroad of COVID-19. Issue 114 (November 2020) - Rodríguez, Yhojan; Novelli, Lucia; Rojas, Manuel; De Santis, Maria; Acosta-Ampudia, Yeny; Monsalve, Diana M.; Ramírez-Santana, Carolina; Costanzo, Antonio; Ridgway, William M.; Ansari, Aftab A.; Gershwin, M. Eric; Selmi, Carlo; et al.
Abstract: Coronavirus disease 2019 (COVID-19) has been categorized as evolving in overlapping phases. First, there is a viral phase that may well be asymptomatic or mild in the majority, perhaps 80% of patients. The pathophysiological mechanisms resulting in minimal disease in this initial phase are not well known. In the remaining 20% of cases, the disease may become severe and/or critical. In most patients of this latter group, there is a phase characterized by the hyperresponsiveness of the immune system. A third phase corresponds to a state of hypercoagulability. Finally, in the fourth stage organ injury and failure occur. Appearance of autoinflammatory/autoimmune phenomena in patients with COVID-19 calls attention for the development of new strategies for the management of life-threatening conditions in critically ill patients. Antiphospholipid syndrome, autoimmune cytopenia, Guillain-Barré syndrome and Kawasaki disease have each been reported in patients with COVID-19. Here we present a scoping review of the relevant immunological findings in COVID-19 as well as the current reports about autoinflammatory/autoimmune conditions associated with the disease. These observations have crucial therapeutic implications since immunomodulatory drugs are at present the most likely best candidates for COVID-19 therapy. Clinicians should be aware of these conditions in patients with COVID-19, and these observations should be considered in the current development of vaccines. Highlights: Autoimmune and autoinflammatory conditions may be triggered by SARS-CoV-2. Bystander activation and molecular mimicry could explain the appearance of these conditions. In severe and critical patients, a cytokine storm syndrome (CSS) and a hypercoagulable state occur and may overlap. CSS may promote the appearance of autoimmune and autoinflammatory-like conditions. These observations should be considered in the current development of vaccines.